Implementasi Pembelajaran Kitab Ta’lim Muta’alim Untuk Meningkatkan Akhlak Siswa Di MA NW Mengkuru - Muhammad Hanafi; Muh.Herianto; Syamsul Arifin; Sukranudin (Pendidikan Al-Gafari, 2023)
The application of learning the book of Ta'lim Muta'alim is one of the lessons implemented by teachers and students at Raden Fatah Batu Junior High School. The focus of this research is learning the book of Ta'lim Muta'alim, evaluation of learning the book of Ta'lim Muta'alim, and student morals at Raden Fatah Batu Junior High School. Researchers used a qualitative approach using a case study type of research to achieve this goal. Based on this research, it can be stated that this plan is not written as lesson plans in general, but this plan is prepared based on the results of meetings between subject teachers which are held every two weeks. Implementation of Learning the Book of Ta'lim Muta'alim is carried out once a week every Saturday with a duration of one lesson hour. This learning includes three stages as usual learning, namely the opening in the form of tawassul, the core activities in the form of reading and translating the book, and then the final activity of evaluation. Evaluation of learning the book of Ta'lim Muta'alim focuses on observing student morals during the learning process of the book of Ta'lim Muta'alim and outside of learning hours. The teacher always observes how effective students are in behaving and acting toward others. And also evaluate his ability by giving a written test. And also psychomotor in translating books and reading books whether students can or not. The morals students at Raden Fatah Batu Junior High School already understand a lot about adab and many apply it in everyday life. Like, courtesy to teachers, friends, and parents. For example, it can be seen from the words and words of students, that they have started to worship the teacher, and so on.